Plastic Filtration and Decomposition According to Ricochet Filtering Mechanism Using Ideonella sakaiensis - Sankrityayan, Prakhar; Biswas, Sumit (Frontiers in Marine Science, 2022)
Our oceans have been under immense stress due to the deposition and accumulation of marine debris, of which 80% are plastics. Of these, microplastics which are small plastic fragments measuring less than five mm, have been a real bane to the marine fauna, especially the ornamental fishes inhabiting coral reef regions. The multibillion-dollar marine ornamental fish trade depends on these fishes caught from coral reefs. It has often been found that these small fishes are severely affected due to the choking of their gills with microplastics as they are natural filter feeders. To curb the load of plastics in the oceans, and especially in the waters around coral reefs, this study aims to develop a small-scale solution, which could later be scaled up by increasing the size and number of each unit as required. The system has been inspired by the filter-feeding mechanism of manta rays as a basic model for the filtration module. The use of a bacteria named Ideonella sakaiensis, which has been known to decompose plastics inherently is the second level of ideation that has gone into the design. The whole system has been envisaged as a floating system, where the filtration units would be submerged under water and the design of the platform over water would have a provision for self-sustenance, apart from the obvious role in maintaining buoyancy. Each filtration unit has been designed to possess multiple layers of sieving, vortexing and cross-flow filtration with a batch of I. sakaiensis at the end of the unit. To maintain a unidirectional flow of water, a fan would be placed at the end of these filtration units. This system can be a solution to the accumulation of plastics in a localized environment and can be scaled up in terms of size and the number of units to cover a greater area and volume to reduce the menace of plastic pollution. This could be a unique and cost-effective answer to the loss of marine fauna, more specifically ornamental fishes to the curse of microplastics.